Coherent 16 Quadrature Amplitude Modulation (16QAM) Optical Communication Systems - El-Nahal, Fady (Photonics Letters of Poland, 2018)
Coherent optical fiber communications for data rates of 100Gbit/s and beyond have recently been studied extensively primarily because high sensitivity of coherent receivers could extend the transmission distance. Spectrally efficient modulation techniques such as M-ary quadrature amplitude modulation (M-QAM) can be employed for coherent optical links. The integration of multi-level modulation formats based on coherent technologies with wavelength-division multiplexed (WDM) systems is key to meet the aggregate bandwidth demand. This paper reviews coherent 16 quadrature amplitude modulation (16QAM) systems to scale the network capacity and maximum reach of current optical communication systems to accommodate traffic growth. Full Text: PDF References K. Kikuchi, "Fundamentals of Coherent Optical Fiber Communications", J. Lightwave Technol., vol. 34, no. 1, pp. 157-179, 2016. CrossRef S. Tsukamoto, D.-S. Ly-Gagnon, K. Katoh, and K. Kikuchi, "Coherent Demodulation of 40-Gbit/s Polarization-Multiplexed QPSK Signals with16-GHz Spacing after 200-km Transmission", Proc. OFc, Paper PDP29, (2005). DirectLink K. Kikuchi, "Coherent Optical Communication Technology", Proc. OFC, Paper Th4F.4, (2015). CrossRef J. M. Kahn and K.-P. Ho, "Spectral efficiency limits and modulation/detection techniques for DWDM systems", IEEE J. Sel. Topics Quantum Electron., vol. 10, no. 2, pp. 259–272, (2004). CrossRef S. Tsukamoto, K. Katoh, and K. Kikuchi, "Coherent demodulation of optical multilevel phase-shift-keying signals using homodyne detection and digital signal processing", IEEE Photon. Technol. Lett., vol. 18, no. 10, pp. 1131–1133, (2006). CrossRef Y. Mori, C. Zhang, K. Igarashi, K. Katoh, and K. Kikuchi, "Unrepeated 200-km transmission of 40-Gbit/s 16-QAM signals using digital coherent receiver", Opt. Exp., vol. 17, no. 32, pp. 1435–1441, (2009). CrossRef H. Nakashima, Et al., "Digital Nonlinear Compensation Technologies in Coherent Optical Communication Systems", Proc. OFC, Paper W1G.5, (2017). CrossRef S. J. Savory, "Digital filters for coherent optical receivers", Opt. Exp., vol. 16, no. 2, pp. 804–817, (2008). CrossRef D. S. Millar, T. Koike-Akino, S. Ö. Arık, K. Kojima, K. Parsons, T. Yoshida, and T. Sugihara, "High-dimensional modulation for coherent optical communications systems", Opt. Express, vol. 22, no. 7, pp 8798-8812, (2014). CrossRef R. Griffin and A. Carter, "Optical differential quadrature phase-shift key (oDQPSK) for high capacity optical transmission", Proc. OFC, Paper WX6, (2002). DirectLink K. Kikuchi, "Digital coherent optical communication systems: fundamentals and future prospects", IEICE Electron. Exp., vol. 8, no. 20, pp. 1642–1662, (2011). CrossRef F. Derr, "Optical QPSK transmission system with novel digital receiver concept", Electron Lett., vol. 27, no. 23, pp. 2177–2179, (1991). CrossRef R. No’e, "Phase noise tolerant synchronous QPSK receiver concept with digital I&Q baseband processing", Proc. OECC, Paper 16C2-5, (2004). <a class="file" href="https://ei.uni-paderborn.de/fileadmin/elektrotechnik/fg/ont/docs/auto/publication/Phase_noise_tolerant_synchronous_QPSK_receiver_concept_with_digital_IampQ_baseband_processing_.pdf" target="_parent"> DirectLink D.-S. Ly-Gagnon, S. Tsukamoto, K. Katoh, and K. Kikuchi, "Coherent detection of optical quadrature phase-shift keying signals with carrier phase estimation", J. Lightw. Technol., vol. 24, no. 1, pp. 12–21, (2006). CrossRef M. Taylor, "Coherent detection method using DSP for demodulation of signal and subsequent equalization of propagation impairments", IEEE Photon. Technol. Lett., vol. 16, no. 2, pp. 674–676, (2004). CrossRef S. Tsukamoto, K. Katoh, and K. Kikuchi, "Unrepeated transmission of 20-Gb/s optical quadrature phase-shift-keying signal over 200-km standard single-mode fiber based on digital processing of homodyne-detected signal for Group-velocity dispersion compensation", IEEE Photon. Technol. Lett., vol. 18, no. 9, pp. 1016–1018, (2006). CrossRef S. Tsukamoto, Y. Ishikawa, and K. Kikuchi, "Optical Homodyne Receiver Comprising Phase and Polarization Diversities with Digital Signal Processing", Proc. ECOC, Paper Mo4.2.1, (2006). CrossRef K. Kikuchi and S. Tsukamoto, "Evaluation of Sensitivity of the Digital Coherent Receiver", J. Lightw. Technol., vol. 20, no. 13, pp. 1817–1822, (2008). CrossRef S. Ishimura and K. Kikuchi, "Multi-dimensional Permutation Modulation Aiming at Both High Spectral Efficiency and High Power Efficiency", Proc. OFC/NFOEC, Paper M3A.2, (2014). CrossRef F. I. El-Nahal and A. H. M. Husein, "Radio over fiber access network architecture employing RSOA with downstream OQPSK and upstream re-modulated OOK data", (Optik) Int. J. Light Electron Opt., vol. 123, no. 14, pp: 1301-1303, (2012). CrossRef T. Koike-Akino, D. S. Millar, K. Kojima, and K. Parsons, "Eight-Dimensional Modulation for Coherent Optical Communications", Proc. ECOC, Paper Tu.3.C.3, (2013). DirectLink B. Sklar, Digital communications: Fundamentals and Applications, Prentice-Hall, (2001).